Maritime economics - Stopford, Martin (Routledge, 2009)
Employs historical and theoretical analysis as the framework for a practical explanation of how shipping works. This book includes chapters on markets, shipping costs, accounts, ship finance, the return on capital, the geography of sea trade, trade theory and specialised cargoes, the merchant fleet shipbuilding, and the regulatory regime.